2011
DOI: 10.1002/mds.23921
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Parkinson's disease: A population‐based prospective study (NEDICES)

Abstract: Most studies of mortality in Parkinson's disease have been clinical studies, yielding results that are not representative of the general population. We assessed the risk of mortality from Parkinson's disease in the Neurological Disorders in Central Spain (NEDICES) study, a prospective population-based study in which Parkinson's disease patients who were not ascertained through medical practitioners were also included. The cohort consisted of 5262 elderly subjects (mean baseline age, 73.0 years), including 81 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 42 publications
2
70
1
1
Order By: Relevance
“…Parkinson's disease (PD) patients have shortened survival when compared with age-matched controls [1][2][3][4]. Several risk factors negatively impact PD survival including demographic factors, such as older age at onset [1]; PD factors, such as psychosis, dementia, and motor severity [4,5]; and non-PD factors, such as pneumonia and cachexia [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson's disease (PD) patients have shortened survival when compared with age-matched controls [1][2][3][4]. Several risk factors negatively impact PD survival including demographic factors, such as older age at onset [1]; PD factors, such as psychosis, dementia, and motor severity [4,5]; and non-PD factors, such as pneumonia and cachexia [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors negatively impact PD survival including demographic factors, such as older age at onset [1]; PD factors, such as psychosis, dementia, and motor severity [4,5]; and non-PD factors, such as pneumonia and cachexia [3]. Very few PD patients survive beyond 20 years, particularly those who develop PD in their seventh or eighth decades.…”
Section: Introductionmentioning
confidence: 99%
“…To address this question, we utilized data from the Neurological Disorders in Central Spain (NEDICES) Study, in which participants were followed for a median of 12.5 years, after which the death certificates of those who died were examined. [10][11][12][13][14][15][16][17][18][19][20] METHODS Study population. Data were derived from the NEDICES Study, a longitudinal, population-based survey of the epidemiology of major age-associated conditions of the elderly, including Parkinson disease, essential tremor, stroke, and dementia.…”
mentioning
confidence: 99%
“…Data were derived from the NEDICES Study, a longitudinal, population-based survey of the epidemiology of major age-associated conditions of the elderly, including Parkinson disease, essential tremor, stroke, and dementia. [10][11][12][13][14][15][16][17][18][19][20] A detailed account of the NEDICES study population and sampling methods has been published. [21][22][23] The survey area consisted of 3 communities: (1) Las Margaritas (approximately 14,800 inhabitants), a working-class neighborhood in Getafe (Greater Madrid); (2) Lista (approximately 150,000 inhabitants), a professional-class neighborhood in the Salamanca district (Central Madrid); and (3) Arévalo (approximately 9,000 inhabitants), an agricultural zone of Arévalo County (located 125 km northwest of Madrid).…”
mentioning
confidence: 99%
“…According to clinical and clinicopathologic studies, MSA, PSP, and CBD share a comparably short survival time of about 7-8 y from symptom onset or less than 3-4 y from clinical diagnosis (1)(2)(3)(4)(5)(6)(7)(8). Survival in PD is distinctly better: although some population-based studies did not find higher mortality (9), others convincingly demonstrated an increased age-adjusted mortality in PD (10,11). As in APS (1,2,5,8), higher age at onset is also associated with a higher PD mortality (9,10), but median survival time was still 10.3 y in a recent population-based cohort with a high average age of 70 y at diagnosis (9).…”
mentioning
confidence: 99%